Low‐grade systemic inflammation biomarkers in sedentary young healthy adults are not significantly affected by a 24‐week concurrent training intervention - Vázquez-Lorente, Héctor; Herrera-Quintana, Lourdes; Acosta, Francisco M.; Amaro-Gahete, Francisco J.; Ruiz, Jonatan R. (John Wiley & Sons, 2025)
In this study, we measured the dose-response effect of a 24-week concurrent training (CT) intervention on low-grade systemic inflammation biomarkers in sedentary young healthy adults. A total of 100 untrained participants were randomized to (1) no exercise (control group, n = 35), (2) aerobic + resistance exercise (CT) at moderate intensity (exercise-moderate group; n = 33), or (3) CT at vigorous intensity (exercise-vigorous group, n = 32). Serum concentrations of C-reactive protein (CRP), interleukin-6 (IL-6), IL-7, IL-8, and IL-10, interferon-gamma (IFN-γ), tumor necrosis factor-α, leptin, and adiponectin were determined and compared among the three groups. The exercise-vigorous group members had lower differences in IL-7 levels among them, compared to the exercise-moderate group members (Δ = -7.97% vs. 1.90%; p = 0.030; 95% CI [-0.90, -0.04]). The exercise-vigorous group members showed higher differences in CRP values (Δ = 20.1%; F = 3.339; p = 0.046) compared to both the control (Δ = -1.91%) and the exercise-moderate (Δ = -23.3%) group members, whereas the control group exhibited higher differences in IFN-γ levels compared to the exercise-vigorous group (Δ = 15.3% vs. 2.62%; p = 0.048; 95% CI [-0.68, -0.01]). For individuals in the three groups, body composition and physical fitness correlated overall with leptin. The data show, and we concluded, that the training intervention had no significant effect on low-grade systemic inflammation biomarkers.